Transient Magnetothermal Neuronal Silencing Using the Chloride Channel Anoctamin 1 (TMEM16A) - Munshi, Rahul; Qadri, Shahnaz M.; Pralle, Arnd (Frontiers in Neuroscience, 2018)
Determining the role and necessity of specific neurons in a network calls for precisely timed, reversible removal of these neurons from the circuit via remotely triggered transient silencing. Previously, we have shown that alternating magnetic field mediated heating of magnetic nanoparticles, bound to neurons, expressing temperature-sensitive cation channels TRPV1 remotely activates these neurons, evoking behavioral responses in mice. Here, we demonstrate how to apply magnetic nanoparticle heating to silence target neurons. Rat hippocampal neuronal cultures were transfected to express the temperature gated chloride channel, anoctamin 1 (TMEM16A). Spontaneous firing was suppressed within seconds of alternating magnetic field application to anoctamin 1 (TMEM16A) channel expressing, magnetic nanoparticle decorated neurons. Five seconds of magnetic field application leads to 12 s of silencing, with a latency of 2 s and an average suppression ratio of more than 80%. Immediately following the silencing period spontaneous activity resumed. The method provides a promising avenue for tether free, remote, transient neuronal silencing in vivo for both scientific and therapeutic applications.